Investigating the socio-economic and epidemiological risk factors associated with TB transmission in a high TB and HIV burdened community in Cape Town, South Africa - Tadokera, Rabecca (Department of Public Health and Family Medicine, 2018)
Background: While several studies have studied the associations between biological factors such as HIV-status with TB transmission or clustering, our understanding of the associations between TB transmission and socio-economic risk factors for TB remains incomplete. More studies are required to enhance our understanding, and hence inform targeted interventions to curb TB transmission, particularly in high burden communities. This study aimed to explore the associations between TB transmission and socio-economic risk factors in one such high TB and HIV burdened community. Methods: A cross-sectional molecular epidemiology study was conducted among adult TB patients resident in a geographically well-defined peri-urban township of Cape Town between 2001 and 2010. Following informed consent, clinical and demographic data were extracted from TB registers and clinical folders. Additional socio-economic data were collected using interviewer-administered questionnaires that were designed to capture data on TB history, TB contacts, socio-economic conditions such as occupation, income level, educational level, sexual behaviour, sexual history in addition to other social and demographic data. M.tb isolates from TB patients were previously analysed using IS6110-based RFLP. Strains with <6 copies of IS6110 (low bandwidth strains) are known to be poorly differentiated and so were excluded from analysis. Composite variables were generated for the social and economic factors using a scoring algorithm to create a "social score" and an "economic score". Data was analysed using StataCorp version 12 software. Bivariate associations and adjusted binary logistic regression analyses were performed to determine associations between TB transmission and the social/economic score in addition to other risk factors that were studied. Results: Of the 509 participants who had complete data available, 352 (69%) were classified as clustered while the remaining 157 participants (31%) were classified as non-clustered. Our analysis showed that clustered cases were more likely to have stayed for a longer period in the study community, (OR=1.06, C.I: 1.02 to 1.10, p=0.006). Clustered cases were also more likely to have stayed in the same house for longer, (median=3 years vs. 2 years, p=0.06) and to live in more crowded conditions as shown by the size of the house and number of rooms used for sleeping (p=0.038). While the evidence was weak, there was a tendency towards a positive association between a high social score and clustering (OR=1.39, C.I: 0.94; 2.03, p=0.08). Conversely, there was a moderate negative association between a high economic score and clustering (OR=0.69, C.I: 0.45; 1.06, p=0.09). Conclusions: While the association between poverty (poor socio-economic status) and TB transmission is not new, the association between TB transmission and prolonged stay within a high burdened community that we report in this study is novel. Our findings further suggest that even in poorer communities there is a "sliding-scale of poverty", with individuals at the lower end of the economic scale being at greater risk for acquiring TB infection and that targeted interventions to address TB transmission in such high burdened communities may be required.